African debts and Chinese receivables. Making sense of a conflict - (:unkn) unknown (My University, 2024)
China, it is argued, has embarked on a debt diplomacy, and has set a trap for developing countries to fall into – a “debt-trap diplomacy” to quote Brahma Chellaney. This vision has been widely adopted by the Trump administration, which has ipso facto made it an accepted truth even if it is not proven. This purely political interpretation is supported by the difficulty of assessing the indebtedness of developing countries to China, a difficulty resulting from the vagueness of the statistical data, the ambiguous interpretations and the terminological jargon used. And while the World Bank is beginning to disseminate apparently reliable statistical data more systematically, thus allowing for more nuanced and less political reflection, China is in turn instrumentalizing them and politicizing its discourse by claiming a de-Westernization of global governance.
Keywords: African Research